Domestic Space in the Times of Change: the Collapse of the USSR, 1985-2000s - (:unkn) unknown (My University, 2019)
This dissertation examines the ways urban domestic spaces transformed under the pressure of social upheaval related to the collapse of the USSR in 1991. The collapse of the Soviet Union has been examined from a standpoint of spatial changes, but existing studies are limited to public spaces and city-scale transformations. In other words, the collapse of the USSR remains a virtually uninvestigated event from the perspective of ordinary places integral for the study of social change in everyday life, such as apartment homes, courtyards, and residential streets. Between the late 1980s and 2000s, an unprecedented remodeling and home improvement boom took place inside Soviet standardized apartments. As a result of these changes in apartment layouts and functional zones, there were also dramatic shifts in identities, cultural practices, and attitudes towards domestic spaces. My work relies on archives, interviews, building codes, and field studies done in Kyiv, Ukraine in order to demonstrate that the demand for change seen in everyday life and domestic architecture predated the 1991 collapse of the USSR. Chapters are organized under domestic practices, such as eating and sleeping, rather than room-labels or apartment building types. This approach embraces a great variety of apartment buildings that existed in the late- and post-Soviet period without extensive focus on differences, but rather explores the overwhelming similarities in the spatial thinking of apartment dwellers and professional architects alike. My research demonstrates that despite their fascination with the West, post-Soviet urbanites did not produce domestic spaces that resembled their Western counterparts, nor did they reproduce the Soviet understanding of home despite the persistence of Soviet infrastructure. Instead, they created their own model of apartment living. The newly acquired freedom to transform one’s home became a characteristic trait of the post-Soviet urban life, while the practice of domestic remodeling determined the everyday life experiences of post-Soviet urbanites.
Keywords: architectural history; change; cultural practices; domestic architecture; everyday life; post-Soviet